An Empirical Study on Ad Hoc Performance of DSRC and Wi-Fi Vehicular Communications. (28th November 2013) - Lee, Seungbae; Lim, Alvin
Abstract : The primary motivation for developing vehicular safety applications is to provide information and assistance required to avoid collisions. Such applications depend on performance of vehicular communications which have critical requirements for various operating scenarios. However, there is still a lack of practical performance measurement data in the open literature that can be used to design robust and reliable applications for vehicle safety. This paper provides an overview of the current standards for vehicular communications and requirements for vehicular applications and analyzes ad hoc performance of commercial off-the-shelf DSRC and Wi-Fi radios in real vehicular environments. Also, it identifies important effects of messages size, message frequency, weather condition, and vehicle mobility on vehicular communications. For example, rainy weather significantly diminishes the communication range and vehicle mobility causes temporal variations in communication throughput. With a better comprehensive understanding of these effects on performance and reliability, quality of vehicular applications can be significantly improved.